The Impact of Inflation, Money Supply, and Interest Rates on Economic Growth: Panel Data Evidence from ASEAN-5 Countries (2014–2024) - Bambang Perkasa Alam; Sumaryoto; Sumarni (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Economic growth is a key indicator of macroeconomic performance and is influenced by various monetary factors. This study aims to examine the effects of inflation, money supply (M2), and interest rates on economic growth in ASEAN-5 countries during the 2014–2024 period. The study employs a quantitative approach using balanced panel data consisting of 55 observations from Indonesia, Malaysia, Singapore, Thailand, and the Philippines. The data were obtained from secondary sources, including the World Bank and the International Monetary Fund (IMF). Panel data regression analysis was conducted using EViews 13, with model selection based on the Chow and Hausman tests. The empirical results indicate that the Fixed Effect Model is the most appropriate estimation model. The findings reveal that inflation has a positive and statistically significant effect on economic growth, suggesting that moderate inflation is associated with increased economic activity. In contrast, the money supply (M2) does not have a significant effect on economic growth during the study period. Furthermore, interest rates have a negative and significant effect, indicating that higher borrowing costs tend to reduce investment and slow economic expansion. The model explains approximately 93.0% of the variation in economic growth, demonstrating strong explanatory power. These findings highlight the importance of maintaining macroeconomic stability through balanced inflation and interest rate policies while improving the effectiveness of monetary transmission to support sustainable economic growth in ASEAN-5 countries.